HPLC Quantification of Glucosamine Sulfate in Eggshell membranes from White and Brown Chicken Eggs - Nora Mady; Nada Mostafa; Maha El-Batsh; Abdelfattah Saoud; Abdel-Nasser Singab (Ain Shams University, 2022)
Eggshell membrane (ESM), a thin membrane lining the eggshell of chicken eggs, is a natural byproduct attracting the attention of many researchers worldwide due to its valuable composition and beneficial biological activities. Its main active ingredients include collagen (types I, V, X), glucosamine sulfate, chondroitin/dermatan sulfate, and hyaluronic acid, so it possesses a beneficial value for maintaining healthy joints. Variation in eggshell color/breed of hens has been reported to affect the quality and composition of eggs and eggshells. So, the current study aimed to compare glucosamine sulfate content in ESM separated from white and brown eggs using the HPLC technique and UV detection at 195 nm. The peak area quantification method was used to determine the concentration of glucosamine in both samples. Results revealed that ESM separated from white eggs has a higher content of glucosamine sulfate (11.83% w/w) than ESM separated from brown eggs (10.68% w/w). We conclude that the use of ESM from white eggs may be more valuable than ESM from brown eggs in further biological studies to determine the effect of ESM in the prevention and management of osteoarthritis.